ASSESSMENT AND DEVELOPMENT DIRECTIONS OF THE INFLUENCE OF INVESTMENT FACTORS ON INCREASING THE COMPETITIVENESS OF THE ECONOMY OF THE KHORAZM REGION (Marketing Journal, 2025)
This article analyzes the importance of investments in ensuring the economic competitiveness of the Khorezm region, their structural structure, dynamics and key influencing factors. It also considers the possibilities of stimulating regional economic growt h by improving the investment climate.
Keywords: Competitiveness; investment; economic growth; foreign investment; infrastructure; regional development